Development of MOOC: a beginner’s guide to Microsoft 365 for novice learners - Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina; Kechil, Rafizah; Mohamed Yusoff, Syarifah Adilah; Johan, Elly Johana; Warris, Saiful Nizam (Penerbit UiTM (UiTM Press), 2026)
This study focuses on the development of a documented guideline named Massive Open Online Course (MOOC): “ A Beginner’s Guide to Microsoft Office 365,” designed specifically for novice learners. With the increasing reliance on cloud-based productivity tools in both educational and professional settings, proficiency in Microsoft Office 365 has become essential. Thus, this research adopts a design-based research approach to guide the systematic planning and development of MOOC, integrating instructional design principles such as the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The course content includes Microsoft Office 365 applications such as Word, Excel and PowerPoint, presented through engaging videos, interactive activities, and assessments, ensuring that materials were accessible, engaging, and aligned with the learning principles. Overall, the development process emphasized iterative design, which can contribute to best practices in MOOC development for digital skills training, particularly in supporting learners with minimal prior exposure to productivity tools like Microsoft Office 365.